INTEGRATING LEXICAL AND GRAMMATICAL KNOWLEDGE THROUGH CARD GAMES - Hairil Yakin; Ridha Fadillah (ENGLISH, 2026)
The integration of lexical and grammatical knowledge remains a persistent challenge for learners of English as a Foreign Language (EFL). While previous studies have explored the use of card games to enhance discrete language skills, limited qualitative attention has been given to students’ internal strategies and perceived challenges when integrating vocabulary and grammar simultaneously, particularly in Islamic secondary school contexts. This qualitative case study investigates students’ strategies and challenges in integrating lexical and grammatical knowledge through card game media at MTs Noor Aini Banjarmasin. Data were collected through semi-structured interviews with four ninth-grade students and classroom observations conducted across three instructional sessions. Thematic analysis revealed two dominant strategies: Lexical-Led Construction, in which learners prioritize word meaning before grammatical arrangement, and Structural Patterning, in which learners employ sentence frameworks prior to lexical insertion. Major challenges included grammatical complexity, unfamiliar vocabulary, and time pressure. Peer collaboration emerged as the primary coping mechanism, facilitating scaffolding and reducing language anxiety. The findings suggest that card games function not merely as motivational tools but as pedagogical mediators that foster lexicogrammatical integration through collaborative learning. This study contributes qualitative evidence to game-based language learning and offers pedagogical implications for EFL classrooms.